Study Protocol: Using Deep-Brain Stimulation, Multimodal Neuroimaging and Neuroethics to Understand and Treat Severe Enduring Anorexia Nervosa - Park, Rebecca J.; Scaife, Jessica C.; Aziz, Tipu Z. (Frontiers in Psychiatry, 2018)
Abstract Background: Research suggests that altered eating and the pursuit of thinness in Anorexia Nervosa is, in part, a consequence of aberrant reward circuitry. The neural circuits involved in reward processing and compulsivity overlap significantly and this has been suggested as a transdiagnostic factor underpinning obsessive compulsive disorder, addictions and eating disorders. The nucleus accumbens is central to both reward processing and compulsivity. In previous studies, deep brain stimulation to the accumbens has been shown to result in neural and symptomatic improvement in both obsessive disorder and addictions. Moreover, in rats, deep brain stimulation to the nucleus accumbens medial shell increases food intake. We hypothesise that deep brain stimulation to the nucleus accumbens may be of benefit in severe and enduring Anorexia, but first feasibility and ethical standards need to be established. The aims of this study are: 1: To provide feasibility and preliminary efficacy data on deep brain stimulation to the nucleus accumbens as a treatment for severe and enduring Anorexia Nervosa. 2: To assess any subsequent neural changes. 3: To develop a neuro-ethical gold standard to guide applications of this treatment. Method: This is a longitudinal study of 6 individuals with Anorexia Nervosa > 7 years. It includes an integrated neuro-ethical sub-study. Deep brain stimulation will be applied to the nucleus accumbens and we will track mechanisms underpinning Anorexia Nervosa using magnetoelectroencephalography, neuropsychological and behavioural measures. Serial measures will be taken on each intensively studied patient pre- and post- deep brain stimulator insertion. This will allow elucidation of the processes involved in symptomatic change over a 15 month period, including a double-blind crossover phase of stimulator on/off. Discussion: Novel, empirically-based treatments for severe and enduring Anorexia Nervosa are urgently needed due to high morbidity and mortality costs. If feasible and effective, deep brain stimulation to the nucleus accumbens could be game-changing in the management of this condition. A neuro-ethical gold standard is crucial to optimally underpin such treatment development. Registration: The study is on-going and registered with clinicaltrials.gov. (https://clinicaltrials.gov/ct2/show/NCT01924598, July 22 2013). It has full ethical and HRA approval (Project ID 128658).